Penyelidikan dan Penyidikan Korban KDRT Yang Dilakukan Artis Public figure Ditinjau Dari Kuhap - Meivani, Deti (Jurnal Ilmiah Wahana Pendidikan, 2024)
Every family definitely yearns for a safe, comfortable and peaceful life. However, it cannot be denied that family life can occasionally present conflicts due to misunderstandings or discrepancies between one family member and another. The existence of this conflict often ends in acts of domestic violence. The main objective of this research is to find out the process of investigating and investigating domestic violence experienced by Public figure Artists and the criminal sanctions imposed on perpetrators of domestic violence. This type of research is normative legal research with the Case Approach, Conceptual Approach and Statue Approach approaches. The source of research material comes from primary sources, namely Law no. 23 of 2004 and secondary sources, namely related literature. Collecting research data through literature study with data analysis techniques through qualitative descriptive analysis. The results of the study prove: 1) For the acts of domestic violence committed by Artist Public figure FI against his wife, the East Java Regional Police Ditreskrimum investigators indicted a number of articles in the law. No. 23 of 2004 article 44 and article 45. In accordance with Article 44 Paragraph 2 where the act which causes the victim to fall ill or seriously injured, is subject to imprisonment for a maximum of 10 years or a maximum fine of IDR 30,000,000.00.” 2) Investigators detain Public figure FI after being examined by a doctor and fingerprint examination to ensure that Public figure FI committed domestic violence against his wife, namely Public figure Artist VM. Investigators determined the detention of FI Public figure Artists in accordance with Article 21 of the Criminal Procedure Code as an objective condition for investigators, where "An order for detention or further detention is carried out against a suspect or defendant who is strongly suspected of having committed a crime based on sufficient evidence.